2019
DOI: 10.20452/pamw.14871
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of stearoyl-CoA desaturase (SCD1) in the adipose tissue contributes to serum content of monounsaturated fatty acids (MUFA) in patients with chronic kidney disease

Abstract: The aim of the present study was to clarify whether the activity of SCD1 in adipose tissue contributes to the increased content of serum MUFA in patients with CKD. Moreover, gene expression of SREBP-1c in adipose tissue was assessed to get further insight into the mechanisms responsible for the observed alterations in serum MUFA profile in those patients. Methods Plasma samples were collected from 46 patients with CKD stage 5 (predialysis and dialyzed), as well as from 57 controls without CKD. Subcutaneous adi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…A research scheme showing the recruitment of study subjects and collection of biological material from them is presented as a supplementary Figure S1. The characteristics of these patients had been reported previously [2,8]. Blood samples were taken after overnight fasting from all the study subjects.…”
Section: Study Groupmentioning
confidence: 99%
See 1 more Smart Citation
“…A research scheme showing the recruitment of study subjects and collection of biological material from them is presented as a supplementary Figure S1. The characteristics of these patients had been reported previously [2,8]. Blood samples were taken after overnight fasting from all the study subjects.…”
Section: Study Groupmentioning
confidence: 99%
“…FA profiles were analyzed by gas chromatography-mass spectrometry (GC-MS) using QP-2010SE apparatus (Shimadzu, Kyoto, Japan), as described previously [2,8].…”
Section: Fatty Acid Determinationmentioning
confidence: 99%
“…CKD promotes FA disorders by metabolic alterations and dietary restrictions resulting from chronic intoxication. Previous research has shown changes in the proportion of individual serum FAs in CKD patients; in particular, the content of serum monounsaturated FAs (MUFAs) is increased [6], and the content of n-3 polyunsaturated FAs (PUFAs) is decreased [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%